Project Management Green Commitment in PMI, Saudi Arabia: How Green Intellectual Capital, Green HRM, Green Training and Innovativeness Influence Project Performance - Alharbi, Bandar Fahad M (Journal of Ecohumanism, 2025)
The study examined the influence of top management green commitment (TMGC) on green intellectual capital (GIC) and its subsequent impact on green human resource management (GHRM) and project performance. Additionally, the study explored the moderating effects of green innovativeness and green training on project management performance within the Saudi Project Management Institute (PMI). Utilizing a cross-sectional design, data were collected from 478 project managers through structured survey questionnaires. Structural equation modeling (SEM) was employed to analyze the relationships among the variables. The results demonstrated a significant positive impact of top management's green commitment to green intellectual capital, which positively influenced green human resource management and project performance. Green innovativeness was identified as the most influential moderator, highlighting its critical role in enhancing project performance. However, the interaction between green innovativeness and green human resource management revealed a negative yet significant moderating effect, suggesting potential complexities in aligning innovation with HR strategies. The research emphasizes the essential role of green practices in improving project management performance, offering novel insights within the Saudi context. These findings address a gap in the existing literature and advocate for the wider adoption and refinement of green strategies in project management practices.